A Clinical Framework for Functional Recovery in a Person With Chronic Traumatic Brain Injury: A Case Study. Issue 3 (July 2017) - McCain, Karen; Shearin, Staci
Abstract : Background and Purpose: This case study describes a task-specific training program for gait walking and functional recovery in a young man with severe chronic traumatic brain injury. Case Description: The individual was a 26-year-old man 4 years post–traumatic brain injury with severe motor impairments who had not walked outside of therapy since his injury. He had received extensive gait training prior to initiation of services. His goal was to recover the ability to walk. Intervention: The primary focus of the interventions was the restoration of walking. A variety of interventions were used, including locomotor treadmill training, electrical stimulation, orthoses, and specialized assistive devices. A total of 79 treatments were delivered over a period of 62 weeks. Outcomes: At the conclusion of therapy, the client was able to walk independently with a gait trainer for approximately 1km (over 3000 ft) and walked in the community with the assistance of his mother using a rocker bottom crutch for distances of 100m (330 ft). Discussion: Specific interventions were intentionally selected in the development of the treatment plan. The program emphasized structured practice of the salient task, that is, walking, with adequate intensity and frequency. Given the chronicity of this individual's injury, the magnitude of his functional improvements was unexpected. Video Abstract available for additional insights from the Authors (see Video, Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A175 ). Abstract : Supplemental Digital Content is Available in the Text.